Sustainability of SMEs In Madiun City: The Role of Business Networks and Absorptive Capacity - Ardianus Laurens Paulus; Vinsensius Widdy Tri Prasetyo (University of Merdeka Malang, 2024)
The sustainability of SMEs is greatly influenced by the role played by business networks and absorptive capacity in absorbing and exploiting new knowledge and market opportunities. This article discusses the influence of business networks on business sustainability, as well as the role of absorptive capacity in connecting the two. This research focuses on SMEs in Madiun City with 60 respondents surveyed. Smart PLS 3.0 is used as an analysis tool. The results show that business networks have a positive and significant effect on absorptive capacity and business sustainability. However, absorptive capacity does not have an impact on business sustainability. In addition, absorptive capacity does not act as a mediator between business networks and business sustainability, indicating that business networks have a direct influence on business sustainability. Thus, this article not only provides valuable insights for academics but also for business practitioners and policy makers who are interested in improving the micro-enterprise ecosystem at the local level in the context of local economic development, especially in Madiun City, East Java.